Exploring of Resilience Skill as Competence on Employee Contextual Performance - Iwan Sidharta (LPPM STMIK Mardira Indonesia, 2024)
The research explored the dimensions of resilience skill as a competence on employee contextual performance. To explore the dimensions of resilience skill as a competence on employee contextual performance, the author employed a survey approach among retail employees in Bandung. The sample consisted of 74 employees who willingly participated in the study. The model's predictions were tested using non-parametric PLS-SEM, preceded by validity and reliability testing of the research instruments. The results of exploring the dimensions of resilience skill as a competence on employee contextual performance revealed that all dimensions significantly impacted employee contextual performance. It is essential to acknowledge the limitations of this research, which include the focus on resilience as a competence and the use of a limited sample size through a cross-sectional survey. These limitations suggest that the findings may only be generalizable to some contexts. Further research is needed to explore other competencies and consider longitudinal studies for a more comprehensive understanding of the relationship between resilience, self-efficacy, and contextual performance.